Molecular and structural changes in gelatin evidenced by Raman microspectroscopy. (April 2018) - Duconseille, Anne; Gaillard, Cédric; Santé-Lhoutellier, Véronique; Astruc, Thierry
Abstract: The gelatin used for the hard capsules manufacturing must meet strict dissolution specification to ensure the delivery of drugs at right time in the digestive tract. However, the environment of production and storage time affect the quality of gelatin dissolution. This study aimed to identify the mechanisms underlying the geographical environment of production and aging impact on the gelatin dissolution rate. Gelatins from 3 different origins of production (A, B & C), whose dissolution rate had been previously characterized, were analyzed by Raman microspectroscopy before and after aging. The principal component analysis (PCA) clearly separated the aged gelatins from non-aged ones. The spectra interpretation suggested the denaturation of gelatin triple-helices. In addition, the formation of cross-links such as dityrosine, glucosyl-galactosylhydroxylysinonorleucine and proteoglycan-like sugar adducts was strongly suspected. Whatever the gelatin aging state, PCA systematically separated the B-gelatins from A and C-gelatins. Pentosidine cross-link was likely to vary depending on the production origin. Finally, the quality of dissolution was discriminated for aged gelatins of A-origin: the non-compliant gelatins exhibited higher lipid content than the compliant ones. Graphical abstract: Image 1 Highlights: High temperature and humidity storage conditions alter the gelatin triple-helices. Cross-link formation is suspected under a high temperature and humidity storage. Geographical environment of gelatin production affects its cross-link content. A higher lipid content reduces the gelatin dissolution rate under production origin.